2018
DOI: 10.1029/2018sw001886
|View full text |Cite
|
Sign up to set email alerts
|

The Reported Durations of GOES Soft X‐Ray Flares in Different Solar Cycles

Abstract: The Geostationary Orbital Environmental Satellites (GOES) Soft X‐ray (SXR) sensors have provided data relating to, inter alia, the time, intensity, and duration of solar flares since the 1970s. The GOES SXR Flare List has become the standard reference catalogue for solar flares and is widely used in solar physics research and space weather. We report here that in the current version of the list there are significant differences between the mean duration of flares which occurred before May 1997 and the mean dur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Data are taken from the GOES X-ray sensor reports (XRS) (https:// www.ngdc.noaa.gov/stp/space-weather/solar-data/solar-features/ solar-flares/x-rays/goes/xrs/, which contain information on flare magnitudes, the timing of the start, peak, and end of the flare, and solar coordinates of the eruption. See, for example, Swalwell et al (2018) for information on how these parameters are defined. All data entries were used, provided the event times were recorded.…”
Section: Shortwave Fadeoutmentioning
confidence: 99%
“…Data are taken from the GOES X-ray sensor reports (XRS) (https:// www.ngdc.noaa.gov/stp/space-weather/solar-data/solar-features/ solar-flares/x-rays/goes/xrs/, which contain information on flare magnitudes, the timing of the start, peak, and end of the flare, and solar coordinates of the eruption. See, for example, Swalwell et al (2018) for information on how these parameters are defined. All data entries were used, provided the event times were recorded.…”
Section: Shortwave Fadeoutmentioning
confidence: 99%
“…Events are shown in Figures 1, 2, and 3, which give a synoptic view of the SEP peak‐intensity power‐law size distribution. Some of the X‐ray fluence values of Figure 1 were computed from incorrect flare onset and end times (Swalwell et al., 2018), but that result is not relevant to our exploration of a new scoring methodology.…”
Section: Data Analysis: the Proton Prediction Systemmentioning
confidence: 99%
“…The solar energetic particle (SEP) events are often tend to be accelerated by the solar flares and coronal mass ejections-driven shocks [35] [67] [18]. These fast moving energetic protons and associated magnetic field are the main cause for geo and space-weather effects such as electronic damages on satellites [49], radian hazards for polar flights, astronauts, and outages of the power grids [5].The prolonged acceleration of the SEPs mainly depends on different types of accelerating mechanism, source locations and free available magnetic energy [19] [69]. It is generally accepted that the short duration SEP events are accelerated by solar flares [54] [66], and the long duration SEP events are related with CMEs-driven shocks [43].…”
Section: Introductionmentioning
confidence: 99%
“…Later many authors found that the peak intensity of SEPs correlated with both speed and width of the associated CMEs [36] [66] [25] [59] [15] [63]. Significant number of authors pointed out that duration of the solar flares is important parameter to predict the space weather events [9] [40] [69]. [9] divided the SEP associated solar flares into two groups: impulsive and gradual (long duration) solar flares during 1978 -1983.…”
Section: Introductionmentioning
confidence: 99%